Guía didáctica “Investiga Biología” para el aprendizaje de biología en estudiantes de primer ciclo paralelos a y b de enfermería de la Universidad Católica de Cuenca, período junio-noviembre 2016. - Durazno Montesdeoca, Gloria Cecilia (2017)
The didactic guide is an instrument that has a technical orientation for the student, and presents thematic contents that favor the development of activities to promote learning. Since Biology is a basic science in the formation of the Nursing Career and because it does not have any didactic material to support its learning, this research work was carried out with the objective of applying the didactic guide "Research Biology" to The learning of biology in nursing students of the Catholic University of Cuenca, the sample is constituted by the universe, which are all students enrolled in the first cycle parallel A and B of the race; The methodology that was used is the Experimental method, to evaluate the learning of Biology through various didactic strategies like the Classroom Project, Laboratory Practices and Collaborative Works, the same ones that were applied to the students during the development of the classes; The technique used is Observation. The data were obtained through instruments such as pre and post application tabs of the didactic guide. The information was processed in the SPSS 22 program, obtaining frequency and percentage tables. The results demonstrated the impact of the didactic guide in the learning process of Biology. In conclusion, when applying different methodological strategies in the teaching-learning process, these benefited the student while allowing the development of skills, favored communication between peers and stimulated research.